Malaria parasite DNA-harbouring vesicles activate cytosolic immune sensors - BOWIE, ANDREW (My University, 2017)
STING is an innate immune cytosolic adaptor for DNA sensors that engage malaria parasite ( Plasmodium falciparum ) or other pathogen DNA. As P. falciparum infects red blood cells and not leukocytes, how parasite DNA reaches such host cytosolic DNA sensors in immune cells is unclear. Here we show that malaria parasites inside red blood cells can engage host cytosolic innate immune cell receptors from a distance by secreting extracellular vesicles (EV) containing parasitic small RNA and genomic DNA. Upon internalization of DNA- harboring EVs by human monocytes, P. falciparum DNA is released within the host cell cytosol, leading to STING-dependent DNA sensing. STING subsequently activates the kinase TBK1, which phosphorylates the transcription factor IRF3, causing IRF3 to translocate to the nucleus and induce STING-dependent gene expression. This DNA-sensing pathway may be an important decoy mechanism to promote P. falciparum virulence and thereby may affect future strategies to treat malaria.
Keywords: Malaria